The Persistence of Civil Militias in Banten and Lampung, Indonesia - Gabriel Facal (Kawalu: Journal of Local Culture, 2019)
This study focuses on how civil militias in Banten and Lampung do their persistence in society. Civil militias play significant role in society not only as being intermediaries between civil societies themselves and the government, but also as a mediator between the different political levels of society: In addition, the existence of martial arts groups give contributions as initiation bases for the activist masses. This study on civil militias also shows how political parallel networks compete for power, beyond the parties and political chairs.